Structural basis of cargo recognition by the myosin-X MyTH4–FERM domain - Hirano, Yoshinori (Nature Publishing Group, 2011)
Myosin-X is an important unconventional myosin that is critical for cargo transportation to filopodia tips and is also utilized in spindle assembly by interacting with microtubules. We present a series of structural and biochemical studies of the myosin-X tail domain cassette, consisting of myosin tail homology 4 (MyTH4) and FERM domains in complex with its specific cargo, a netrin receptor DCC (deleted in colorectal cancer). The MyTH4 domain is folded into a helical VHS-like structure and is associated with the FERM domain. We found an unexpected binding mode of the DCC peptide to the subdomain C groove of the FERM domain, which is distinct from previously reported β–β associations found in radixin–adhesion molecule complexes. We also revealed direct interactions between the MyTH4–FERM cassette and tubulin C-terminal acidic tails, and identified a positively charged patch of the MyTH4 domain, which is involved in tubulin binding. We demonstrated that both DCC and integrin bindings interfere with microtubule binding and that DCC binding interferes with integrin binding. Our results provide the molecular basis by which myosin-X facilitates alternative dual binding to cargos and microtubules.